2020
DOI: 10.3389/fimmu.2020.601089
|View full text |Cite
|
Sign up to set email alerts
|

From Chickens to Humans: The Importance of Peptide Repertoires for MHC Class I Alleles

Abstract: In humans, killer immunoglobulin-like receptors (KIRs), expressed on natural killer (NK) and thymus-derived (T) cells, and their ligands, primarily the classical class I molecules of the major histocompatibility complex (MHC) expressed on nearly all cells, are both polymorphic. The variation of this receptor-ligand interaction, based on which alleles have been inherited, is known to play crucial roles in resistance to infectious disease, autoimmunity, and reproduction in humans. However, not all the variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…Eight of these genes have functions of interest: MHCIBF2, CLDN7, SIRT5, ENTPD1, SYT7, SLC22A23, S100B and MUC4 . The MHCIBF2 ( Major histocompatibility complex class I antigen BF2 ) gene is the predominant ligand of cytotoxic T lymphocytes [58]. It has been shown that a particular MHC I haplotype may contribute to control the response to SE infection in chicken [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Eight of these genes have functions of interest: MHCIBF2, CLDN7, SIRT5, ENTPD1, SYT7, SLC22A23, S100B and MUC4 . The MHCIBF2 ( Major histocompatibility complex class I antigen BF2 ) gene is the predominant ligand of cytotoxic T lymphocytes [58]. It has been shown that a particular MHC I haplotype may contribute to control the response to SE infection in chicken [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…The peptide is mainly anchored at the P1, P4, P6 and P9 pockets of MHC-II ( 19 , 21 ). Examples of non-canonical peptide anchor positions have been reported both for human pMHC-I ( 22 ) and pMHC-II ( 23 ), and for some other species’ pMHC-I ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently a correlation has been identified between the expression level of BF2 alleles and the diversity of their peptide repertoire. Alleles that are highly expressed have a narrower range of bound peptides (fastidious alleles) while the peptide repertoire is much broader in alleles with lower expression (promiscuous alleles) 12,13 . Humans have an essentially fixed number of three polymorphic classical (class Ia) genes, HLA‐A, B, and C, and three less‐polymorphic non‐classical (class Ib) genes, HLA‐E, F, and G—which are all known to interact with NK cell receptors 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, different MHC class I alleles can have more dissimilar expression, peptide binding profiles, and ultimately functions than can currently be predicted by peptide binding motifs alone. Consequently, the concept of allele supertypes based on sequence alone likely contains an additional layer of complexity than has previously been considered 13 …”
Section: Introductionmentioning
confidence: 99%